A case of intra-arterial thrombolysis with alteplase in a patient with hypothenar hammer syndrome but without underlying aneurysm. (3rd January 2018) - Shukla, Harshal; Yaghdjian, Vicken; Koleilat, Issam
Hypothenar hammer syndrome is a cause of symptomatic ischemia of the hand secondary to the formation of aneurysm or thrombosis of the ulnar artery in the setting of a complete or incomplete palmar arch. Acute occlusive thrombus or embolus of the hand represents a complex problem that often may require immediate surgical intervention. We report a case of acute unilateral arterial hand ischemia requiring catheter-directed thrombolysis with Alteplase therapy in a patient with acute occlusive arterial thrombosis of the left ulnar artery. A catheter-directed thrombolytic regimen consisted of Alteplase 1 mg/h for 24 h, and heparin was infused through the sheath side arm at a rate of 500 units per hour for resolution of the thrombus and improvement in symptoms. A former truck driver presented with worsening pain and subsequent development of significant cyanosis with early gangrenous changes of the left second and third fingertips. He had significant callous of the hypothenar eminence and reported that his left hand was not only his "driving" hand but also a cane has been used in his left hand to ambulate. Initial angiogram revealed only ulnar artery occlusion at the wrist with reconstitution just distal to the hypothenar eminence. After 24 h of the initiation of thrombolysis, repeat angiography revealed resolution with a widely patent ulnar artery. His symptoms and the color of his digits immediately improved, and within a few months, his hand had normalized. The patient had no clinical sequelae of thrombolytic therapy. Catheter-directed thrombolytic therapy in situations of acute occlusive thrombus of the hand may provide a therapeutic option for patients with suspected hypothenar hammer syndrome. However, thrombolytic therapy carries risk of significant hemorrhagic complications. Before initiating therapy, careful judgment about the possibility for bleeding risk is required. This provides for a minimally invasive alternative to open surgical revascularization especially in the absence of underlying correctable anatomic defect such as aneurysm.